2018
DOI: 10.1101/276253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalable approximate Bayesian inference for particle tracking data

Abstract: Many important datasets in physics, chemistry, and biology consist of noisy sequences of images of multiple moving overlapping particles. In many cases, the observed particles are indistinguishable, leading to unavoidable uncertainty about nearby particles' identities. Exact Bayesian inference is intractable in this setting, and previous approximate Bayesian methods scale poorly. Non-Bayesian approaches that output a single "best" estimate of the particle tracks (thus discarding important uncertainty informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…All ground truth for training comes only from simulation. Realistic synthetic, semi-synthetic or augmented datasets have been key to cracking other challenging problems in neurosicence [26][27][28][29][30][31] and have already shown promising potential for tracking neurons [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All ground truth for training comes only from simulation. Realistic synthetic, semi-synthetic or augmented datasets have been key to cracking other challenging problems in neurosicence [26][27][28][29][30][31] and have already shown promising potential for tracking neurons [17].…”
Section: Introductionmentioning
confidence: 99%
“…All ground truth for training comes only from simulation. Realistic synthetic, semi-synthetic or augmented datasets have been key to cracking other challenging problems in neurosicence ( Parthasarathy et al, 2017 ; Yoon et al, 2017 ; Sun et al, 2018 ; Lee et al, 2020 ; Mathis and Mathis, 2020 ; Pereira et al, 2020 ) and have already shown promising potential for tracking neurons ( Wen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…See e.g. (Parthasarathy et al, 2017, Yoon et al, 2017, Weigert et al, 2018, Sun and Paninski, 2018 for previous applications of similar ideas to image denoising and decoding problems.…”
Section: Detectionmentioning
confidence: 99%